Analisis Peran I’rab dalam Menerjemahkan Mubtada’-Khobar Fi’il-Fa’il dari Bahasa Arab ke Indonesia (International Forum of Researchers and Lecturers, 2025)
This study analyzes the role of i'rab in translating mubtada’-khobar and fi’il-fa’il structures from Arabic into Indonesian. Using a qualitative approach and descriptive analysis, this research examines how i'rab, as a system of final vowel changes in Arabic, influences grammatical and semantic functions in the translation process. The theoretical review focuses on the concept of i'rab according to Ibn Ajurrum and Eugene Nida's dynamic equivalence theory, which emphasizes the importance of accurately transferring meaning and grammatical structure. The literature review method involves collecting, analyzing, and synthesizing sources from classical Arabic grammar books, previous research, and modern translation theories. The data is analyzed comparatively to identify effective translation patterns in adapting Arabic syntactic structures into Indonesian. The findings indicate that a deep understanding of i'rab plays a crucial role in translation, especially since Indonesian does not have a similar system. To convey the grammatical information embedded in i'rab, translators must adjust word order, use pronouns, or adapt sentence structures. This article provides new insights into how i'rab affects Arabic-Indonesian translation and its implications for improving translation skills.